Some Double Sequence Spaces of Fuzzy Real Numbers of Paranormed Type - Bipul Sarma (Journal of Mathematics)
We study different properties of convergent, null, and bounded double sequence spaces of fuzzy real numbers like completeness, solidness, sequence algebra, symmetricity, convergence-free, and so forth. We prove some inclusion results too.